Mechanical and Functional Properties of Unwashed Barramundi (Lates calcarifer) Gels as Affected by High-Pressure Processing at three Different Temperatures and Salt Concentrations. Issue 4 (20th April 2020) - Truong, Binh Quang; Buckow, Roman; Nguyen, Minh
ABSTRACT: Changes in gelling properties of unwashed barramundi gels with 1% and 2% added salt, then pressurized at 300, 400, and 500 MPa at ≤10°C and 50°C for 10 min were studied. Pressure-induced unwashed barramundi gels exhibited a lower gel strength and poorer mechanical properties, such as lower hardness and springiness, as compared to heat-induced gels. Comparable water holding capacity to heat-induced gels was only obtained at 2% salt concentration and ≥400 MPa pressure. Scanning electron microscope images also showed that barramundi minced muscle with 2% added salt and pressurized at ≥400 MPa had a finer microstructure with smoother surface compared to heat-induced gels.